Interleukin-10 polymorphisms and susceptibility to ARV associated hepatotoxicity. (August 2019) - Singh, HariOm; Samani, Dharmesh; Nain, Sumitra; Dhole, T.N.
Abstract: Interleukin-10 (IL-10) is an anti-inflammatory cytokine associated with the inhibition of HIV replication. IL-10 polymorphisms were found to be linked to drug-induced hepatotoxicity. Hence we examined the prevalence of IL-10 (-819C/T, -1082A/G) polymorphisms in a total of 165 HIV patients which included 34 patients with hepatotoxicity, 131 without hepatotoxicity and 155 healthy controls by the PCR-RFLP method. In HIV patients with hepatotoxicity, the IL - 10 -819TT genotype increased the risk of ARV associated hepatotoxicity severity (OR = 1.61, P = 0.35). IL - 10 -819TT genotype was overrepresented in patients with hepatotoxicity as compared to healthy controls (26.5% vs. 13.5%, OR = 1.61, P = 0.46). IL - 10 -819CT genotype was associated with advance HIV disease stage (OR = 0.49, P = 0.045). In HIV patients without hepatotoxicity, the IL - 10 -819TT genotype was more prevalent in patients consuming tobacco as compared to non-users (OR = 1.60, P = 0.41). In HIV patients without hepatotoxicity using both alcohol + efavirenz along with IL-10 -819CT genotype resulted in increased risk for the acquisition of ARV associated hepatotoxicity (OR = 4.00, P = 0.36). In multivariate logistic regression, taking nevirapine was associated with the risk hepatotoxicity severity (OR = 0.23, P = 0.005). In conclusion, an insignificant association between IL-10 polymorphisms and susceptibility to ARV associated hepatotoxicity. Highlights: IL-10 polymorphisms did not differ significantly among HIV patients and healthy controls. IL - 10 -819CT genotype was found significantly lower in advance HIV disease stage compared to healthy controls. IL-10 -819CT genotype increased the risk for the acquisition of ARV-associated hepatotoxicity in alcohol and Efavirenz users. An insignificant association between IL-10 polymorphisms and susceptibility to ARV associated hepatotoxicity were detected.